Production Management Based on the Qur'an and Hadith for the Sustainability of the Sharia Economy - Ade Vieea Syantana; Seri Hidayu; Khairunnisa; Elsa Salsabila (Al-Fadilah: Islamic Economics Journal, 2024)
Production management in Islam, based on the Qur'an and Hadith, presents a relevant approach to supporting the sustainability of the Islamic economy. This article analyzes Islamic principles that encompass environmental sustainability, work ethics, and social responsibility in production activities. Based on the study of Qur'anic verses and Hadith, it is found that production management must be carried out wisely to avoid waste, maintain ecological balance, and meet quality standards in accordance with Sharia. The concept of halalan thayyiban encourages the creation of products that are not only halal but also of high quality, safe, and environmentally friendly. Additionally, the principle of justice in the distribution of production results, such as through zakat, infak, and sadaqah, contributes to economic equity and social welfare. The implementation of this management requires collaboration between the government, businesses, and society to create an inclusive, fair, and sustainable production system. Thus, the approach based on Islamic values can be a solution to address global challenges, such as resource exploitation, social inequality, and environmental damage, while also supporting the goals of sustainable development